2022
DOI: 10.3389/fneur.2022.939318
|View full text |Cite
|
Sign up to set email alerts
|

Altered cortical thickness, degree centrality, and functional connectivity in middle-age type 2 diabetes mellitus

Abstract: PurposeThis study aimed to investigate the changes in brain structure and function in middle-aged patients with type 2 diabetes mellitus (T2DM) using morphometry and blood oxygen level-dependent functional magnetic resonance imaging (BOLD-fMRI).MethodsA total of 44 middle-aged patients with T2DM and 45 matched healthy controls (HCs) were recruited. Surface-based morphometry (SBM) was used to evaluate the changes in brain morphology. Degree centrality (DC) and functional connectivity (FC) were used to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Except for the correlations between rs-fMRI indices, no significant correlation between rs-fMRI indices and clinical parameters or cognitive performance was observed. Studies focusing on T2DM patients without cognitive impairment detected little direct relationship between cognitive performances and rs-fMRI measurements (Liu et al, 2017Kang et al, 2022). A task-fMRI based study indicated mediation effects among olfactory dysfunction, pancreatic function and executive function in T2DM patients without cognitive impairment (Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Except for the correlations between rs-fMRI indices, no significant correlation between rs-fMRI indices and clinical parameters or cognitive performance was observed. Studies focusing on T2DM patients without cognitive impairment detected little direct relationship between cognitive performances and rs-fMRI measurements (Liu et al, 2017Kang et al, 2022). A task-fMRI based study indicated mediation effects among olfactory dysfunction, pancreatic function and executive function in T2DM patients without cognitive impairment (Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…The differences in the node topological properties showing significant differences between the T2DM and HC groups. Functional impairments (represented by DC values) and structural impairments of the precuneus region have been widely reported in T2DM patients (Chen et al, 2015Kang et al, 2022). The precuneus is a highly connected network hub region and an important part of the default mode network, and is involved in many high-order complex cognitive processes (Cavanna and Trimble, 2006).…”
Section: Altered Nodal Properties In Cortical Structural Network In T2dmmentioning
confidence: 99%
“…SBM has been applied to investigate cerebral cortical abnormalities in neuropsychiatric disorders, such as Alzheimer’s disease ( Nho et al, 2012 ), schizophrenia ( Palaniyappan and Liddle, 2012 ), autism ( Nordahl et al, 2007 ), etc. Several studies have recently begun to explore alterations in SBM indices in T2DM patients ( Kang et al, 2022 ; Shao et al, 2022 ). In addition, it has also been demonstrated that cytokines and brain-derived neurotrophic factor (BDNF) levels may be associated with the development of T2DM-related cognitive impairment ( Zhen et al, 2013 ; Simo et al, 2017 ; Sun et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%